Treatment with a Combination of Metformin and 2-Deoxyglucose Upregulates Thrombospondin-1 in Microvascular Endothelial Cells: Implications in Anti-Angiogenic Cancer Therapy - Samson Mathews Samuel (18808246) (2019)
Metformin, the most widely used anti-diabetic drug, also exhibits anti-cancer properties; however, the true potential of metformin as an anticancer drug remains largely unknown. In this study using mouse microvascular endothelial cells (MMECs), we investigated the effects of metformin alone or in combination with the glycolytic inhibitor, 2-deoxyglucose (2DG), on angiogenesis-a process known to be an integral part of tumor growth, cancer cell survival and metastasis. MMECs were exposed to 2DG (1–10 mM) for 48 h in the absence or presence of metformin (2 mM). The status of angiogenic and anti-angiogenic marker proteins, proteins of the mTOR pathway and cell-cycle-related proteins were quantified by Western blot analysis. Assays for cell proliferation, migration and tubulogenesis were also performed. We observed robust up-regulation of anti-angiogenic thrombospondin-1 (TSP1) and increased TSP1-CD36 co-localization with a marked decrease in the levels of phosphorylated vascular endothelial growth factor receptor-2 (pVEGFR2; Y1175) in 2DG (5 mM) exposed cells treated with metformin (2 mM). Additionally, treatment with metformin and 2DG (5 mM) inhibited the Akt/mTOR pathway and down-regulated the cell-cycle-related proteins such as p-cyclin B1 (S147) and cyclins D1 and D2 when compared to cells that were treated with either 2DG or metformin alone. Treatment with a combination of 2DG (5 mM) and metformin (2 mM) also significantly decreased cell proliferation, migration and tubulogenic capacity when compared to cells that were treated with either 2DG or metformin alone. The up-regulation of TSP1, inhibition of cell proliferation, migration and tubulogenesis provides support to the argument that the combination of metformin and 2DG may prove to be an appropriate anti-proliferative and anti-angiogenic therapeutic strategy for the treatment of some cancers. Other Information Published in: Cancers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/cancers11111737